Drug Safety Monitoring Information - Elena V. Shubnikova; Marya A. Darmostukova; Tatyana M. Bukatina (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2020)
Experts of the Department for Evaluation of Medicinal Products' Safety of the Scientific Centre for Expert Evaluation of Medicinal Products analysed administrative decisions of foreign regulatory authorities on the recall of medicines and/or the need to amend the prescribing information due to changes in their safety profile. The analysis helped to identify 11 administrative decisions that contain information on the following medicines registered in Russia: ranitidine, nizatidine, famotidine, pantoprazole, ondansetron, domperidone.